Preparation and antibacterial property of waterborne polyurethane/Zn-Al layered double hydroxides/ZnO nanocomposites - Zhang, W.; Zheng, Y.; Xu, Y.; Yu, Y.; Shi, Q.; Liu, Lihong; Peng, H.; Ouyang, Yousheng (American Scientific Publishers, 2013)
In this work, a novel environmental-friendly waterborne polyurethane/ZnAl-layered doublehydroxides/ZnO nanoparticles composite (WPU/ZnAl-LDHs/ZnO) was synthesized via in-situ polymerization. ZnAl-LDHs and ZnAl-LDHs/ZnO were synthesized by refluxing in an oil bath. In order to disperse ZnAl-LDHs/ZnO homogeneously into WPU matrix, ZnAl-LDHs/ZnO was firstly functionalized by isophorone diisocyanate. The incorporated content of ZnAl-LDHs/ZnO in the composite has profound effect on such physical properties as mechanical strength, thermal stability and water swelling. It is demonstrated that appropriate amount of ZnAl-LDHs/ZnO with good dispersion in the WPU matrix significantly improves the physical performance of the composites. Finally, the antibacterial activity of the composite was tested against G(-) Escherichia coli and G(+) Staphylococcus aureus. The results indicate that WPU incorporated with ZnAl-LDHs/ZnO shows strong antibacterial activity upon contact.